Pengaruh Transformasi Digital Terhadap Kinerja Umkm: Peran Mediasi Kapabilitas Inovasi Dalam Perspektif Dynamic Capability Theory - Basri Basri; Tri Fira Yuniza Fira; Anna Ashrawi Suhartini Anna (Movere Journal, 2026)
This study aims to examine the effect of digital transformation on MSME performance, the effect of digital transformation on innovation capability, the effect of innovation capability on MSME performance, and the mediating role of innovation capability in the relationship between digital transformation and MSME performance from the perspective of Dynamic Capability Theory. This study employed a quantitative approach using an explanatory research design. The population consisted of 1,200 culinary MSMEs in Makassar City, with a sample of 93 respondents determined using the Slovin formula and purposive sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that digital transformation has a positive and significant effect on MSME performance (β = 0.438; p = 0.005) and innovation capability (β = 0.200; p = 0.030). Innovation capability also has a positive and significant effect on MSME performance (β = 0.402; p = 0.007) and significantly mediates the relationship between digital transformation and MSME performance (β = 0.208; p = 0.043). These findings indicate that the success of digital transformation depends not only on technology adoption but also on MSMEs' ability to develop innovation capabilities that create added value and improve sustainable business performance. Keywords: Digital Transformation, Innovation Capability, MSME Performance